Aortitis which developed after the administration of granulocyte-colony stimulating factor. (2nd January 2020) - Mukai, Tomoyuki; Kubo, Shinichiro; Morita, Yoshitaka; Yamamoto, Mari; Ikeda, Masahiko
Abstract: Drug-induced aortitis is rare; thus, the diagnosis of drug-induced aortitis could be delayed unless clinicians are aware of the disease entity. Herein, we describe the case of a 66-year-old woman who developed aortitis after administration of granulocyte-colony stimulating factor (G-CSF) during chemotherapy for her breast cancer. Thickening of the aortic wall was clearly detected by computed tomography (CT) and magnetic resonance imaging. After excluding the other possible aetiologies, an association between G-CSF and the development of aortitis was highly suspected. Corticosteroid treatment rapidly regressed the aortitis, as confirmed by follow-up CT examination. G-CSF analog is generally well tolerated; however, there are limited case reports of G-CSF-associated aortitis, suggesting the causative effect of G-CSF in the development of aortitis. Currently, G-CSF-associated aortitis has received little attention among rheumatologists. As the delayed diagnosis results in irreversible changes in the aorta, not only oncologists but also rheumatologists should be aware of this unrecognized disease entity, G-CSF-associated aortitis.